The Legal Status of MoU as a Contract in BUMN Cooperation Agreements (Study of Denpasar Court Decision Number 419/PDT.G/2012/PN.DPS) - Tanaya, Velliana; Yap, Celine Alexia; Subiran, Danishel; Gunawan, Lauren Angel; Singgih, Marvino Nathanael; Nugraha, Dwi Putra (Dinasti Research, 2025)
Performance is an obligation where one or both parties have the responsibility to fulfill a condition that has been agreed upon in the agreement. However, if a performance is not performed or even violated, it can lead to default. In some instances, default might occur on the basis of a breach to a document that is generally considered non-binding, such as an MoU which turns out to be legally enforceable if it fulfills the elements of a valid agreement. In Denpasar Court Decision Number 419/PDT.G/2012/PN.DPS, the Defendant, a State-owned enterprise (BUMN), was proven to have committed a default. Therefore, there is a need to strengthen regulation and supervision to ensure the accountability of BUMN without hampering their operational independence. This paper uses a normative-empirical research method that examines the practical implementation of legal provisions and observes legal interactions that occur in society. Therefore, The Legal Status of MoU as a Contract in BUMN Cooperation Agreements (Study of Denpasar Court Decision Number 419/PDT.G/PN/DPS) is written